KONTRADIKTIF SANKSI PIDANA DALAM HUKUM PAJAK - Fransiskus Dodi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2013)
This study is focused on the aspect of law enforcement, especially on tax law. The study additionally examines the process of tax laws enforcement that tends to emphasize on the criminal law rather than on administrative one. This research was conducted by using a normative juridical method focused on primary and secondary materials.The result of the research shows that merely emphasizing the criminal aspects of tax law enforcement will only jeopardizes the primary goal of tax administration in collecting tax revenue that is highly needed for public needs such as building schools, bridges, hospitals, fuel subsidies, and so on. Conversely, using an administrative approach will maximize tax revenue because it will make taxpayers and tax officers feel safe every time they face a tax dispute. Key words : Administrative law, criminal law, government spending.